From scratch : writings in music theory - Tenney, James (University of Illinois Press, 2015)
One of the 20th century's most important musical thinkers, James Tenney did pioneering work in multiple fields, including computer music, tuning theory and algorithmic and computer-assisted composition. 'From Scratch' is a collection of Tenney's hard-to-find writings arranged, edited and revised by the self-described 'composer/theorist.'